2018
DOI: 10.1371/journal.pone.0200694
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic architecture and signatures of selection of dual purpose Gir cattle populations using genomic information

Abstract: Gir is one of the main cattle breeds raised in tropical South American countries. Strong artificial selection through its domestication resulted in increased genetic differentiation among the countries in recent years. Over the years, genomic studies in Gir have become more common. However, studies of population structure and signatures of selection in divergent Gir populations are scarce and need more attention to better understand genetic differentiation, gene flow, and genetic distance. Genotypes of 173 ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 87 publications
4
55
2
1
Order By: Relevance
“…The authors used different methods, one of them based on LD and reported that the region of the SLC24A4 gene was common in the two populations, providing strong evidence of selection signatures in the Gir breed. Since high LD over an extended region is likely the result of recent selection (Pérez O’Brien et al, ), the results obtained could explain the findings of Maiorano et al () in Gir cattle populations, highlighting the importance of LD on chromosome 21 for the formation of this breed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The authors used different methods, one of them based on LD and reported that the region of the SLC24A4 gene was common in the two populations, providing strong evidence of selection signatures in the Gir breed. Since high LD over an extended region is likely the result of recent selection (Pérez O’Brien et al, ), the results obtained could explain the findings of Maiorano et al () in Gir cattle populations, highlighting the importance of LD on chromosome 21 for the formation of this breed.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, since the animals of this herd are part of an experimental selection programme, the pedigree file was complete, a fact that may have contributed to the good imputation accuracy. Maiorano et al (), studying the population structure of the same population, showed the formation of a single cluster for animals of this herd, with mating of related animals favouring a reduction in the genetic difference among individuals. The relationship between animals may present inbreeding levels, a factor that may influence the accuracy of imputation.…”
Section: Discussionmentioning
confidence: 95%
“…Differences in the segments of ROH islands on the chromosomes were identified between the two populations. According to the results of principal component analysis and discriminant analysis of principal components shown in of the study of Maiorano et al (), there is a genetic difference between the Bp and Dp populations and this difference reflects the variation that exists between the populations.…”
Section: Resultsmentioning
confidence: 99%
“…According to principal component analysis of the Gyr breed (beef and dairy) depicted in Figure of the study of Maiorano et al (), PC2 shows a more compact cluster in the Bp population, possibly because the population belongs to a closed herd in which few sires are used for mating, increasing the level of kinship and permitting accurate imputation of the genotypes of this population. The Dp population exhibited a more disperse cluster based on PC2, indicating a greater genetic distance and lower kinship between individuals of the population compared with Bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation